PERAN WORLD FOOD PROGRAMME (WFP) DALAM MENANGANI KRISIS PANGAN DI MADAGASKAR MELALUI MADAGASCAR COUNTRY STRATEGIC PLAN (2019-2024) - Karmila, Mila; Saeri, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The World Food Programme is the largest humanitarian organization helping to combat the world's food crisis by providing food aid in emergencies, and working with communities to eliminate malnutrition and build resilience. Madagascar, a low-income country with more than 1.3 million people, faces severe hunger in 2021. In this case, WFP is here to help address the food crisis in Madagascar through the Madagascar Country Strategic Plan (2019-2024). This research uses the International Organization theory and the Group Analysis level. This theory explains how the role of international organizations, which not only makes policies, but must carry out every activity that becomes a policy in fulfilling its responsibilities as an international organization. The research method used is a qualitative method with data collection techniques obtained from literature studies. The results show that the World Food Programme has played an active role in dealing with the problem of the food crisis in Madagascar. Based on the theory of International Organizations put forward by Teuku May Rudi, there are three roles, namely as a forum for cooperation, as a means of negotiation, and as an institution that carries out its work program. First, as a forum, where WFP cooperates with the Government of Madagascar to deal with the food crisis that occurred. Second, WFP as a facilitator of negotiations between the government of Madagascar and the government of Madagascar.